Glucose-activated JMJD1A drives visceral adipogenesis via α-ketoglutarate-dependent chromatin remodeling - Chenxu Yang; Makoto Arai; Eko Fuji Ariyanto; Ji Zhang; Debby Mirani Lubis; Ryo Ito; Shiyu Xie; Mio Nitta; Fuka Kawashima; Tomofumi Ishitsuka; Chaoran Yang; Tomohiro Suzuki; et al. (Cell Reports)
Summary: Adipose tissue remodels via hypertrophy or hyperplasia in response to nutrient status, but the mechanisms governing these expansion modes remain unclear. Here, we identify a nutrient-sensitive epigenetic circuit linking glucose metabolism to chromatin remodeling during adipogenesis. Upon glucose stimulation, α-ketoglutarate (α-KG) accumulates in the nucleus and activates the histone demethylase JMJD1A to remove repressive histone H3 lysine 9 dimethylation (H3K9me2) marks at glycolytic and adipogenic gene loci, including Pparg. JMJD1A is recruited to pre-marked promoter chromatin via nuclear factor IC (NFIC), enabling carbohydrate-responsive element-binding protein (ChREBP) binding and transcriptional activation. This feedforward mechanism couples nutrient flux to chromatin accessibility and gene expression. In vivo, JMJD1A is essential for de novo adipogenesis and hyperplastic expansion in visceral fat under nutrient excess. JMJD1A deficiency impairs hyperplasia, exacerbates adipocyte hypertrophy, and induces local inflammation. These findings define a glucose-α-KG-JMJD1A-ChREBP axis regulating depot-specific adipogenesis and uncover a chromatin-based mechanism by which glucose metabolism governs adaptive adipose tissue remodeling.